The climate change mitigation effects of daily active travel in cities. (April 2021) - Brand, Christian; Dons, Evi; Anaya-Boig, Esther; Avila-Palencia, Ione; Clark, Anna; de Nazelle, Audrey; Gascon, Mireia; Gaupp-Berghausen, Mailin; Gerike, Regine; Götschi, Thomas; Iacorossi, Francesco; Kahlmeier, Sonja; et al.
Highlights: How much CO2 can be saved by walking, cycling and e-biking in towns and cities? Cyclists had 84% lower CO2 emissions from all daily travel than non-cyclists. Life cycle CO2 emissions decreased by 14% for each additional cycling trip. The top 10% of participants were responsible for 59% of life cycle CO2 emissions. Regular cycling was most strongly associated with reduced life cycle CO2 emissions for commuting and social trips. Abstract: Active travel (walking or cycling for transport) is considered the most sustainable form of personal transport. Yet its net effects on mobility-related CO2 emissions are complex and under-researched. Here we collected travel activity data in seven European cities and derived life cycle CO2 emissions across modes and purposes. Daily mobility-related life cycle CO2 emissions were 3.2 kgCO2 per person, with car travel contributing 70% and cycling 1%. Cyclists had 84% lower life cycle CO2 emissions than non-cyclists. Life cycle CO2 emissions decreased by −14% per additional cycling trip and decreased by −62% for each avoided car trip. An average person who 'shifted travel modes' from car to bike decreased life cycle CO2 emissions by 3.2 kgCO2 /day. Promoting active travel should be a cornerstone of strategies to meet net zero carbon targets, particularly in urban areas, while also improving public health and quality of urban life.